2016
DOI: 10.1016/j.juro.2016.02.2879
|View full text |Cite
|
Sign up to set email alerts
|

S&T-50 DOES TRANSPERINEAL PROSTATE BIOPSY REDUCE COMPLICATIONS COMPARED WITH TRANSRECTAL BIOPSY? A SYSTEMATIC REVIEW AND META-ANALYSIS OF RANDOMISED CONTROLLED TRIALS

Abstract: Our preliminary study demonstrates the feasibility of EGFR determination in bladder washings of patients affected by NMIBC after TUR, during adjuvant treatment and subsequent follow-up. A useful pellet was available in more than 85% of patients, with evidence of up-regulation in 36% of them. Within the high risk category, a significant overexpression of EGFR, mean value of 4.16 folds, was detected. EGFR overexpression might identify a subgroup of high risk tumors inclined to progression despite of intravesical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Infectious complications are not only burdensome for patients, but at a mean cost of AUD7362 per admission, 20 it is also a costly experience. Rates of infection post TPB are much reduced compared to transrectal biopsies 3,21,22 making them preferrable in this aspect. Indeed this very reason have led to calls for the transrectal biopsy technique to be abandoned worldwide 23 …”
Section: Discussionmentioning
confidence: 99%
“…Infectious complications are not only burdensome for patients, but at a mean cost of AUD7362 per admission, 20 it is also a costly experience. Rates of infection post TPB are much reduced compared to transrectal biopsies 3,21,22 making them preferrable in this aspect. Indeed this very reason have led to calls for the transrectal biopsy technique to be abandoned worldwide 23 …”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the transperineal technique uses needles that are inserted through the perineum, in a sterile fashion, with sedation, to take 10-12 cores in the lateral, middle, and apical regions of the prostate. Recent studies showed that transperineal biopsy had a comparable detection rate of PCa and fewer complications reported, such as lower infection risk, and better visualization of the apical and anterior prostate area than the transrectal approach [22]. Even though it is only in a small proportion, Indonesian urologists have already started conducting a transperineal biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Many published studies have highlighted the key role of mpMRI before a biopsy in the diagnosis of significant PCa [15] , [16] , [17] . In addition, the traditional TR approach has been called into question, not only because of the supposed increased risk of infection [18] , [19] , but also because mpMRI has made possible the detection of anterior lesions, more accurately detected with the TP approach [20] . Therefore, the TP approach has been presented as the emerging standard for prostate biopsies [14] .…”
Section: Discussionmentioning
confidence: 99%